Offsetting Illegitimacy? How Pressures from Securities Analysts Influence Incumbents in the Face of New Technologies - Benner, Mary J.; Ranganathan, Ram (Academy of Management Journal, 2012)
We study how analysts' recommendations affect firms' strategies during radical technological shifts. We find, from our study of firms in three industries undergoing technological change, that analysts' recommendations trigger changes in strategic investments during periods of uncertain technological change. We also find that firms that make high investments despite negative analysts' recommendations announce a higher value of share repurchases, an action that may offset the growing illegitimacy of these increased investments by signaling alignment with shareholders' interests. Radical technological changes provide a source of exogenous variation that contributes to explanation of how firms balance technological pressures for adaptation and institutional pressures for legitimacy.